Optimization of neon soft X-ray yield in a low-energy dense plasma focus device - M.A., Malek; M.K., Islam; M., Akel; M., Salahuddin; Saw, S. H.; Lee, S. (World Scientific Publishing Co Pte Ltd, 2019)
The modified version of Lee model code is used in numerical experiments for characterizing and optimizing neon soft X-ray yield (Ysxr) of the United Nations University/International Center for Theoretical Physics Plasma Focus Facility (UNU/ICTP PFF) device operated at 14 kV and 30 μF. In our present work, the neon yield Ysxr is improved with an optimized UNU/ICTP PFF device by computing the optimum combination of static inductance (L0), anode length (z0), anode radius (a) and cathode radius (b), keeping fixed their ratio (c=b/a) at 3.368, through a lot of numerical experiments at six operating pressures (P0). At lower P0 (e.g. 2.0, 2.5 and 3.3 Torr), the optimum L0 value, together with the corresponding optimum combination of z0, a and b, is found to be 15 nH, whereas at higher P0 (e.g. 4.0, 5.0 and 6.0 Torr), it is obtained as 10 nH. Though the computed maximum neon yield Ysxr (57.2 J with the corresponding efficiency of 1.94%) is found at P0=4.0Torr, assuming an achievable range of incorporating low-inductance technology, the best optimum combination of L0, z0, a and b is found to be at P0=3.3Torr, resulting in the computed optimum neon yield Ysxr of 54.60 J with a corresponding efficiency of 1.9%. This computed neon yield Ysxr is about 11 times higher than the measured value (5.4±1J) at optimum P0=3.0Torr of UNU/ICTP PFF. It is also observed that our computed neon yield Ysxr is improved by around six times from the previously computed value, which was 9.5 J at the optimum P0=3.5 Torr for optimum anode configuration of this machine. In addition, neon yield Ysxr is obtained with our optimized combination of L0, z0, a and b at 11.5 kV and compared with the measured neon yield Ysxr of the NX2 machine.